1987
DOI: 10.1093/clinchem/33.10.1832
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to porcine uteroferrin used in measurement of human tartrate-resistant acid phosphatase.

Abstract: The immunological similarity between human tartrate-resistant acid phosphatase (EC 3.1.3.2) and porcine uteroferrin previously reported for the isoenzyme from spleens of patients with leukemic reticuloendotheliosis (Ketcham et al., J Biol Chem 1985;260:5768-76) has been confirmed for partly purified acid phosphatase found in the spleen of a patient with Gaucher's disease, and for the corresponding isoenzyme in other tissues and serum. Anti-uteroferrin antibodies raised in rabbits have been used to demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…These cells have a common lineage from myeloid progenitor cells and appear to be immunologically distinct from Langerhans' and splenic dendritic cells that are non-classical Mw. 20 Immunostaining of Mw isolated from both sources using immune-speci®c polyclonal antiuteroferrin antibody showed abundant intracellular staining attributable to TRAP in cells obtained from wildtype animals; 15 as expected, immunostaining was absent in cells from Acp 5 null mice lacking TRAP enzymatic activity ( Fig. 1b, 1c).…”
Section: Immunophenotype Of Trap-de®cient and Wild-type Peritoneal Anmentioning
confidence: 89%
“…These cells have a common lineage from myeloid progenitor cells and appear to be immunologically distinct from Langerhans' and splenic dendritic cells that are non-classical Mw. 20 Immunostaining of Mw isolated from both sources using immune-speci®c polyclonal antiuteroferrin antibody showed abundant intracellular staining attributable to TRAP in cells obtained from wildtype animals; 15 as expected, immunostaining was absent in cells from Acp 5 null mice lacking TRAP enzymatic activity ( Fig. 1b, 1c).…”
Section: Immunophenotype Of Trap-de®cient and Wild-type Peritoneal Anmentioning
confidence: 89%
“…The specificity of the antibody to acid phosphatase has been further confirmed by electrophoresis of an unfractionated extract of Gaucher's disease spleen on SDS(sodium dodecyl sulphate)-polyacrylamide gel followed by probing with anti-uteroferrin antiserum and 1251-labelled protein A. This has shown that the antiserum reacts only with the 37 kDa protein band corresponding to the iron-containing acid phosphatase isoenzyme and with no other protein (Echetebu et al 1987). The cross-reactivity of anti-porcine uteroferrin antibody with rat osteoclastic acid phosphatase was confirmed in the following way.…”
Section: Measurement Of Acid Phosphatase Activitymentioning
confidence: 90%
“…The antibody-isoenzyme complex has been shown to possess markedly reduced catalytic activity. The antiserum or immunopurified antibodies also have been found not to cross-react with other acid phosphatase isoenzymes, including the tartrate-resistant erythrocyte enzyme (Echetebu et al 1987). The specificity of the antibody to acid phosphatase has been further confirmed by electrophoresis of an unfractionated extract of Gaucher's disease spleen on SDS(sodium dodecyl sulphate)-polyacrylamide gel followed by probing with anti-uteroferrin antiserum and 1251-labelled protein A.…”
Section: Measurement Of Acid Phosphatase Activitymentioning
confidence: 91%
See 1 more Smart Citation
“…The anti-human cathepsin D antibody was described previously (Muschol et al 2002). The polyclonal anti-porcine uteroferrin antibody (Echetebu et al 1987) was a kind gift from Dr Cox (University of Cambridge, Cambridge, UK). Secondary horseradish peroxidase-conjugated goat anti-rabbit, goat anti-mouse, and goat anti-rat IgG were obtained from Dianova (Hamburg, Germany).…”
Section: Antibodiesmentioning
confidence: 99%